2008
DOI: 10.1007/s10886-008-9477-4
|View full text |Cite
|
Sign up to set email alerts
|

Protein Expression Changes in Maize Roots in Response to Humic Substances

Abstract: Humic substances are known to affect plant metabolism at different levels. We characterized humic substances extracted from earthworm feces by diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy and used them to treat corn, Zea mays L., seedlings to investigate changes in patterns of root protein expression. After root plasma membrane extraction and purification, proteins were separated by two-dimensional gel electrophoresis, and differential spot intensities were evaluated by image analysis. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 46 publications
6
27
0
Order By: Relevance
“…Effects of humic substances on plant genes and their metabolites have been further characterized in reports using protemotics, trancriptomics, and microarrays. Proteomic analyses of maize roots following applications of humic substances revealed that a total of 42 proteins were differentially expressed by HS, including proteins related to energy, metabolism, and cellular transport (Carletti et al 2008). This study concluded that the major pathways in the roots affected by humic substances were sucrose metabolism, malate dehydrogenase, ATPases, and cytoskeletal proteins.…”
Section: Plant Physiology and Metabolismmentioning
confidence: 99%
“…Effects of humic substances on plant genes and their metabolites have been further characterized in reports using protemotics, trancriptomics, and microarrays. Proteomic analyses of maize roots following applications of humic substances revealed that a total of 42 proteins were differentially expressed by HS, including proteins related to energy, metabolism, and cellular transport (Carletti et al 2008). This study concluded that the major pathways in the roots affected by humic substances were sucrose metabolism, malate dehydrogenase, ATPases, and cytoskeletal proteins.…”
Section: Plant Physiology and Metabolismmentioning
confidence: 99%
“…Carletti et al [47] reported for the first time a proteomic approach in a study on maize seedlings treated with HS. These authors isolated plasma membrane proteins, including triosophosphate isomerase (TIM; EC 5.3.1.1), glyceraldehyde-3-P dehydrogenase (GAPD; EC 1. , and verified whether these were downregulated by the HS treatment.…”
Section: Changes On Primary and Secondary Metabolismmentioning
confidence: 99%
“…This reductionist assay tests for a protein's ability to form an ionic conductance and has been used successfully to address animal annexin transport function (e.g., Burger et al, 1994;Liemann et al, 1996). Phosphatidylethanolamine was used to form bilayers as it is a predominant phospholipid in maize plasma membrane (Bohn et al, 2001;Kukavica et al, 2007) where ANN33 and ANN35 are located (Carletti et al, 2008). Phosphatidylserine was incorporated because annexin binding to phosphatidylserine is a hallmark of this protein family, and cholesterol was used to provide bilayer stability under the ionic conditions used.…”
Section: Highly Purified Zm Ann33/35 Preparation Elevates [Ca 2+ ] Cytmentioning
confidence: 99%
“…This protoplast assay requires annexin addition to the extracellular plasma membrane face. While ANN33/35 are soluble proteins, they also exist in the maize plasma membrane (Hochholdinger et al, 2005;Carletti et al, 2008) and are predicted to be secreted (SecretomeP program; Bendtsen et al, 2004). Thus, the protoplast assay also tests for annexin interaction with a plasma membrane from the extracellular face.…”
Section: Introductionmentioning
confidence: 99%